Bank Competition, Concentration, and Credit Reporting - Bruhn, Miriam (The World Bank, 2013)
This paper explores the empirical relationship between bank competition, bank concentration, and the emergence of credit reporting institutions. The authors find that countries with lower entry barriers into the banking market (that is, a greater threat of competition) are less likely to have a credit bureau, presumably because banks are less willing to share proprietary information when the threat of market entry is high. In addition, a credit bureau is significantly less likely to emerge in economies characterized by a high degree of bank concentration. The authors argue that the reason for this finding is that large banks stand to lose more monopoly rents from sharing their extensive information with smaller players. In contrast, the data show no significant relationship between bank competition or concentration and the emergence of a public credit registry, where banks' participation is mandatory. The results highlight that policies designed to promote the voluntary creation of a credit bureau need to take into account banks' incentives to extract monopoly rents from proprietary credit information